25th International Conference on Software Engineering, 2003. Proceedings. 2003
DOI: 10.1109/icse.2003.1201190
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study of an informal knowledge repository in a medium-sized software consulting company

Abstract: Numerous studies have been conducted on design and architecture of knowledge repositories. This paper addresses the need for looking at practices where knowledge repositories are actually used in concrete work situations. This insight should be used when developing knowledge repositories in the future.Through methods inspired by ethnography this paper investigates how an unstructured knowledge repository is used for different purposes by software developers and managers in a medium-sized software consulting co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Therefore, informal knowledge transfer should be considered to supplement the insufficiency of formal component documentation and specification. This point was showed in other empirical studies as well [6] [10]. For research question RQ4, we found that informal knowledge transfer is especially important in the component reuse.…”
Section: Component Understandingsupporting
confidence: 60%
“…Therefore, informal knowledge transfer should be considered to supplement the insufficiency of formal component documentation and specification. This point was showed in other empirical studies as well [6] [10]. For research question RQ4, we found that informal knowledge transfer is especially important in the component reuse.…”
Section: Component Understandingsupporting
confidence: 60%
“…According to the earlier studies on collaborative digital information repositories, the functional sustainability of a repository is highly dependent on the activity of archive users and the emergence of a culture of collaboration, integration into daily practises, and a critical mass to sustain necessary level of contributions, which obliges others to contribute (Peddibhotla and Subramani 2007;Hollingshead Fulk, and Monge 2002;Dingsøyr and Røyrvik 2003). On the other hand, we suggest that the archive does not need to be updated constantly if its materials are of sufficient significance to some of the users.…”
Section: Discussionmentioning
confidence: 99%
“…In creating a knowledge repository, knowledge is collected, summarized, and integrated across sources". Dingsøyr & Røyrvik (2003) have explained this term as "Experience bases" or "Corporate Memories".…”
Section: Brief Literature Review For the Term 'Knowledge Repository'mentioning
confidence: 99%